Bilateral tunnel vision as the first presenting sign of levamisole-induced vasculitis (Journal of Health Sciences, 2018)
Levamisole-contaminated cocaine is an increasingly reported cause of a syndrome characterized by vasculitic skin lesions and immunologic abnormalities. With approximately 70% of cocaine in the United States now contaminated with levamisole, the incidence of this syndrome is likely to increase. We report the case of a 42 years-old Caucasian woman who presented with fronto-temporal pulsating headache and progressive bilateral loss of vision.